2014
DOI: 10.1016/j.jpolmod.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Housing and the business cycle in South Africa

Abstract: This paper examines the housing-output growth nexus in South Africa by accounting for the time variation in the causal link with a bootstrapped rolling Granger non-causality test. We use quarterly data on real gross domestic product, real house prices, real gross fixed capital formation and number of building plans passed. Our data span 1971Q2-2012Q2. Using full sample bootstrap Granger causality tests, we find a uni-directional causality from output to number of building plans passed; a uni-directional causal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…Notes 1. Large number of studies has reported a strong link between the housing market and the economic activity in the U.S. (see for example Aye et al (2014), Nyakabawo et al (2015), and Emirmahmutoglu et al (2016) for detailed literature reviews in this regard). 2.…”
Section: Resultsmentioning
confidence: 99%
“…Notes 1. Large number of studies has reported a strong link between the housing market and the economic activity in the U.S. (see for example Aye et al (2014), Nyakabawo et al (2015), and Emirmahmutoglu et al (2016) for detailed literature reviews in this regard). 2.…”
Section: Resultsmentioning
confidence: 99%
“…The shred of literature has proven the versatility of housing market and the perceived relationship with handful of macroeconomics (Aye, Balcilar, Bosch, & Gupta, ; Canarella, Miller, & Pollard, ; Cesa‐Bianchi, ; Cesa‐Bianchi, Cespedes, & Rebucci, ; Kishor & Marfatia, ; Nyakabawo, Miller, Balcilar, Das, & Gupta, ; Sirmans, Macpherson, & Zietz, ; Zhang, Li, Hui, & Li, ). Also, the housing market and the financial factors' relationship has been observed over time (Aoki, Proudman, & Vlieghe, ; Case, Quigley, & Shiller, ; Cesa‐Bianchi et al, ).…”
Section: Overview Of Previous Studiesmentioning
confidence: 99%
“…Despite substantial literature modelling the business cycle, literature analysing the linkages between housing, business cycles and policies has been understudied both theoretically and empirically (Leamer, 2007). Aye et al (2014), Ghent and Owyang (2010), Leamer (2007), Iacoviello (2005), Davis and Heathcote (2005) and Kan et al (2004) are in consensus that housing plays an important role in predicting the business cycles, and thus highlighted the importance of considering the movement of the housing market in policy formulation. On the other spectrum, the housing market could be proxied by the house prices (Aye et al , 2014; Iacoviello, 2005; Davis and Heathcote, 2005; Kan et al , 2004) and other housing indicators, such as national permits and residential investment (Ghent and Owyang, 2010; Leamer, 2007), in analysing the link between housing and business cycles.…”
Section: Literature Reviewmentioning
confidence: 99%